Review Article: The Review of Legal Issues Related to the Impacts of Online Vacation Rental Platforms (OVRPs) on Vacation Condominium Rentals and the Hotel Industry in Thailand - Bootvong, Parichart; Dendoung, Than (Journal of Architectural/Planning Research and Studies (JARS), 2018)
This article reviews the impact of Online Vacation Rental Platforms (OVRPs) on vacation condominium rentals and the hotel industry in Thailand and discusses the legal implications of the OVRP use. The literature reviews are providing explanations of Thailand’s laws involving OVRPs and exploring current connections between hotels, vacation condominiums and online rental platforms, using case studies and examples. We find that OVRPs provide short-term rentals in most vacation condominiums at popular tourist destinations in Thailand. According to the Thai Civil and Commercial Code, B.E. 2551, the owners of such properties have the right to lease their property, but rentals of less than 30 days constitute an infringement of the Hotel Act, B.E. 2547. Case studies from other countries suggest that OVRPs may have positive as well as negative impacts on the hotel industry, and may also generate indirect benefits for other industries such as tourism and real estate development. Increasingly, vacation condominiums in Thailand are attracting individual investors, many of them foreigners, for the short-term rental market via OVRPs. This development not only undermines the Hotel Act, B.E. 2547 but also poses various risks for hosts, guests, co-owners and potential condominium buyers – risks which are not currently addressed by applicable Thai law. Areas identified as requiring further research regarding the impacts and legal implications of OVRPs in Thailand include: (i) balance of positive and negative impacts of OVRPs on Thai economy and society; (ii) impacts of OVRPs on the vacation condominium market in Thailand; and (iii) merits of amending the legal issues to cover the OVRPs rentals.